Clinical features of IgG4-related periaortitis/periarteritis based on the analysis of 179 patients with IgG4-related disease: a case–control study - Makiko Ozawa; Yasunari Fujinaga; Junpei Asano; Akira Nakamura; Takayuki Watanabe; Tetsuya Ito; Takashi Muraki; Hideaki Hamano; Shigeyuki Kawa (Arthritis Research & Therapy, 2017)
Abstract Background Immunoglobulin G4-related disease (IgG4-RD) is a newly recognized systemic condition characterized by high serum immunoglobulin G4 (IgG4) concentration and IgG4-bearing plasma cell infiltration in affected organs. Although it has become evident that IgG4-RD also involves the systemic aortic/arterial system, the precise details of this condition remain unclear. The present study sought to clarify the clinical features of IgG4-related periaortitis/periarteritis. Methods Among 223 patients with IgG4-RD, 179 (131 male, median onset age 67 years) were recruited for this study. Periaortitis/periarteritis was defined as vessel wall thickness with circumferential enhancement on contrast-enhanced computed tomography. Results Periaortitis/periarteritis was identified in 65 (36.3%; 53 male) of 179 IgG-RD patients. The distribution of IgG4-related periaortitis/periarteritis could be broadly classified into five types, with the most prevalent Type 2 (44.6%) being localized at the infra-renal artery portion of the abdominal aorta and continuing to the iliac arteries. The infra-renal artery region of the abdominal aorta was most frequently involved (>80%) among IgG4-related periaortitis/periarteritis cases. Comparisons of clinical parameters between IgG4-RD patients with and without periaortitis/periarteritis revealed significantly higher propensities for older IgG4-RD onset age and highly active disease state featuring elevated serum IgG, IgG4, circulating immune complex, and soluble interleukin-2 receptor. All patients showed improvement of wall thickening after steroid therapy, although nine patients (20.9%) exhibited worsening of luminal dilatation. The main risk factor for this manifestation was prior luminal dilatation according to multivariate analysis. Conclusion IgG4-related periaortitis/periarteritis predominantly occurred at the infra-renal artery portion of the abdominal aorta, affected older IgG4-RD onset patients, and was prevalent in highly active disease states. As reported previously, the main risk factor for worsening luminal dilation after corticosteroid therapy was the existence of luminal dilation beforehand.